Drug Abuse Prevention Strategies: A Post-pandemic Approach - Chifamba, Blessing; Chifamba, Constance (Recent Research Advances in Arts and Social Studies Vol. 9, 2024)
This book chapter discusses the causes of the rapid rise in drug abuse and several strategies that may be used to control the rapid rise of drug abuse among adolescents during the COVID-19 pandemic to date (post-pandemic era). The suggested effective strategies are based on the holistic approach model that engages all stakeholders to work collaboratively to implement prevention and intervention strategies as posited by the PROSPER Model. Prosper Model brings together schools, families, communities, and Universities in partnerships that use positive approaches to strengthen families and empower youths to make informed decisions. Keeping adolescents engaged in fruitful activities, empowering them with life skills, and involving the students in volunteer work for vulnerable children will help them resist peer pressure and contribute meaningfully to society.